2006
DOI: 10.1002/jctb.1445
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of growth medium for the production of α‐amylase from Bacillus amyloliquefaciens using response surface methodology

Abstract: The optimization of nutrient levels for the production of α-amylase by Bacillus amyloliquefaciens was carried out using response surface methodology (RSM) based on the 2 3 factorial central composite design (CCD). This procedure limited the number of actual experiments performed while allowing for possible interactions between three components. RSM was adopted to derive a statistical model for the effect of starch, peptone and yeast extract (YE) on α-amylase production. The P-value of the coefficient for linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The fit of the model was also expressed by the coefficient of determination, R 2 , which was 0.9336, indicating that 93% of the variability in the response could be explained by the model. The coefficient of variation (CV) indicates the degree of precision with which the treatments are compared [25,26], and the higher the value of CV the lower the reliability of experiment [27,28]. Here, a lower value of the CV (13.61%) indicates a greater reliability of the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…The fit of the model was also expressed by the coefficient of determination, R 2 , which was 0.9336, indicating that 93% of the variability in the response could be explained by the model. The coefficient of variation (CV) indicates the degree of precision with which the treatments are compared [25,26], and the higher the value of CV the lower the reliability of experiment [27,28]. Here, a lower value of the CV (13.61%) indicates a greater reliability of the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…and a 23 IU/mL of enzyme production was achieved. Statistical optimization of α-amylase production by Bacillus amyloliquefaciens resulted in 17.8 IU/mL (Tanyildizi et al 2006). In the present study, Streptomyces sp.…”
Section: Discussionmentioning
confidence: 54%
“…In general, experimental results were enhanced by the optimization using response surface methodology than the conventional optimization methods. Mahat et al (2004) and Tanyildizi et al (2006) have reported an increase in production yield to 34% and 15%, respectively, using response surface methodology. Improvement in the yield and production can also be enhanced using response surface methodology.…”
Section: Figurementioning
confidence: 99%